2010
DOI: 10.1097/mbc.0b013e3283389513
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the factor VII gene and ischemic stroke in young adults

Abstract: Polymorphic configurations of the coagulation factor VII gene (F7) are associated with plasma levels of FVII antigen (FVII:Ag) and FVII coagulant activity (FVII:C). Our aim was to determine whether F7 polymorphisms influence risk of ischemic stroke in young adults. One hundred and fifty survivors of ischemic stroke before the age of 45 and an equal number of age and sex-matched controls were genotyped for five F7 polymorphisms: the -A670C transversion, -323 decanucleotide insertion (P + 10), the number (which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
0
23
1
Order By: Relevance
“…The allele -402 G/A has been independently associated with the increased transcriptional activity of FVII (Lopaciuk et al, 2010). The allele -401 G/T is significantly associated with lower plasma levels of FVII (Eroğlu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The allele -402 G/A has been independently associated with the increased transcriptional activity of FVII (Lopaciuk et al, 2010). The allele -401 G/T is significantly associated with lower plasma levels of FVII (Eroğlu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined these polymorphisms in patients with venous and arterial thrombosis, but the results are very variable and sometimes contradictory (Athanasiadis et al, 2010;Lopaciuk et al, 2010;Eroğlu et al, 2010Eroğlu et al, , 2011Previtali et al, 2011;Friso et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the majority of case-control studies demonstrated no association between predictors of venous thromboembolism and increased stroke risk (4,22). Notably, even in stroke patients with cardiac right-to-left shunt, there was no increased prevalence of thrombophilic diathesis (22,31). So far, thrombophilia work-up regarding the arterial system has been predominantly focused on the diagnosis of antiphospholipid syndrome (9).…”
Section: Zusammenfassungmentioning
confidence: 99%